Instrument engineers' handbook - Lipták, Béla G.; Eren, Halit (Professor of electrical engineering) (CRC/Taylor & Francis, 2003)
Unsurpassed in its coverage, usability, and authority since first published in 1969, the three-volume ""Instrument Engineers' Handbook"" continues to be the premier reference for instrument engineers around the world. It helps users select and implement hundreds of measurement and control instruments and analytical devices and design the most cost-effective process control systems that optimize production and maximize safety. ""Volume 1: Process Measurement and Analysis"" now enters its fourth edition, fully updated and with increased emphasis on installation and maintenance consideration. Its